The phonetic values of the Tibetan letter r in Tibeto-Chinese transcriptional texts from Dunhuang - Coblin, W. South (2024)
In Tibeto-Chinese transcriptions from Dūnhuáng, Tibetan r frequently occurs in syllable final position, where it corresponds to final -t of the traditional Qièyùn System. This use of Tibetan r in the texts has been well known for over a century and is often discussed in the literature. Much rarer and less well known is the use of r in syllable initial and medial positions. In this paper it is noted that syllable initial r- occurs exclusively in certain phrase-final particles and corresponds to Qièyùn System initial l-, while medial -r- is limited to a small number of Division II-type syllables. In these latter cases, it may indicate some sort of rhotacism.